2009
DOI: 10.1002/chem.200801223
|View full text |Cite
|
Sign up to set email alerts
|

Protein Flexibility and Metal Coordination Changes in DHAP‐Dependent Aldolases

Abstract: The mobility of rhamnulose-1-phosphate aldolase (RhuA) was analysed with a normal mode description and high level calculations on models of the active site. We report the connection between the mobility and the chemical properties of the active site, and compare them to a closely related enzyme, fuculose-1-phosphate aldolase (FucA). Calculations show that the different coordination number for the zinc ion, reported in the crystal structures of RhuA and FucA, was due to a different spatial arrangement of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Determination of the actual energy differences between transition states would require of accurate quantum mechanics calculations. However, it seems plausible that since the geometries of the transition states for the CÀC bond formation reactions are similar to those of the aldolase adduct complexes, [41] the DE syn-anti values of Table 2 could correlate with the energy differences for the corresponding transition states. Therefore, these results would suggest lower activation barriers for the anti adducts and, consequently, a kinetic preference for these, which could explain the formation of larger proportions of anti products from aldehydes (R)-2 c or (R)-2 d. If this can be extended to the other aldehydes, it would provide an explanation to the experiments carried out at low temperature.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Determination of the actual energy differences between transition states would require of accurate quantum mechanics calculations. However, it seems plausible that since the geometries of the transition states for the CÀC bond formation reactions are similar to those of the aldolase adduct complexes, [41] the DE syn-anti values of Table 2 could correlate with the energy differences for the corresponding transition states. Therefore, these results would suggest lower activation barriers for the anti adducts and, consequently, a kinetic preference for these, which could explain the formation of larger proportions of anti products from aldehydes (R)-2 c or (R)-2 d. If this can be extended to the other aldehydes, it would provide an explanation to the experiments carried out at low temperature.…”
Section: Resultsmentioning
confidence: 95%
“…Similar geometries were obtained for the adducts derived from (R)-2 c and (R)-2 d. This arrangement resembles that found in the crystal structure of RhuA-phosphoglycolohydroxamate complex (PDB 1GT7), in which a water molecule coordinates the cation in addition to the two oxygen atoms from the ligand. In a very recent paper in which high-level computations have been used to study the enzymatic mechanisms of RhuA and FucA, JimØnez et al [41] have shown that in the transition state for the C À C formation step, a negative charge builds up on the aldehyde oxygen atom, which is stabilized by interaction with the positive charge of the Zn 2 + , and that this interaction is maintained by the aldol product.…”
Section: Resultsmentioning
confidence: 98%
“…These enzymes catalyse the reversible cleavage of two epimers, rhamnulose‐1‐phosphate and fuculose‐1‐phosphate, respectively, yielding dihydroxyacetone phosphate (DHAP) and L‐lactaldehyde. They have very similar active sites, accommodating a Zn 2+ ion, which coordinates DHAP and facilitates the abstraction of a proton from the α ‐carbon to form an enol during the condensation reaction (Jiménez, Clapés, & Crehuet, ). In the Zn 2+ ‐bound form, neither of them has a detectable oxygenase activity.…”
Section: How Slow Is Rubisco?mentioning
confidence: 99%
“…Crystallographic studies with a transition state analogue have revealed that, despite the similarity of their active site residues, the Zn 2+ ion is pentacoordinated in FucA, whereas it is hexacoordinated in RhuA, with a H 2 O molecule acting as the sixth ligand (Joerger, Mueller‐Dieckmann, & Schulz, ; Kroemer, Merkel, & Schulz, ). Presumably, this leads to slight differences in the geometry of coordinating residues around the metal (Jiménez et al, ). Protein environments are known to be able to modify the electronic properties of bound metals or cofactors through a network of interaction with the “second sphere” and via indirect H‐bonds (Lee & Lim, ; Maret, ; Williams, ).…”
Section: How Slow Is Rubisco?mentioning
confidence: 99%
“…In particular, changes in the coordination of the zinc atom in class II aldolases appear to allow the binding and release of substrates ( Figure 2). [81] Hence, domain movements and the coordination chemistry of the active site metal suggest an explanation of why these enzymes have similar experimental turnover rates. [81] Hence, domain movements and the coordination chemistry of the active site metal suggest an explanation of why these enzymes have similar experimental turnover rates.…”
Section: Structure and Mechanismmentioning
confidence: 97%